LITOTRIPSI LASER HOLMIUM YAG UNTUK TERAPI BATU URETER - Adi, Kuncoro; Safriadi, Ferry; Sugandi, Suwandi; Haroen, Zulhardi; Noegroho, Bambang S; Tjahjodjati, Tjahjodjati (Indonesian Urological Association, 2008)
Objective: To assess the efficacy of pulsed holmium:YAG laser lithotripsy for ureteral stone therapy. Material and method: Ninety-one patients (70 males and 21 females) with age range 20 – 76 years underwent 93 ureteroscopic procedures for 101 ureteral stones. A preoperative diagnosis was established by ultrasound scanning and intravenous urography. An 8 F rigid Karl-Storz ureteroscope was used for a holmium:YAG laser (OmniPulse MaxTM 80 watt Holmium Laser System Model 1210-VHP, Trimedyne,Inc. Irvine CA, USA) as energy source for laser lithotripsy. The stone localization was mostly at the lower third of the ureter. The mean stone size was 9,6 mm, mean duration of procedure was 48,1 minutes, and the mean hospital stay was 2,1 days. Results: The overall stone clearance rate was 95,6% with the best results for stones in the middle third of the ureter (100%). At follow up we noted two patients with residual stones and two patients with a perforation of the ureteral wall. Conclusion: The Holmium:YAG laser is effective for ureteral stone treatment with a high success rate. Special attention and care should be afforded in impacted ureteral stones.